2001
DOI: 10.1002/1097-0142(20010901)92:5<1288::aid-cncr1450>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgery and chemotherapy on the quality of life of younger women with breast carcinoma

Abstract: BACKGROUND Studies that prospectively and simultaneously evaluate, within the first year of diagnosis, the impact of surgery and chemotherapy on quality of life (QOL) of younger women (60 years or younger) with early stage breast carcinoma are limited. METHODS Quality of life of 103 women who had surgery (lumpectomy, 49; mastectomy, 54) approximately 1 month before the start of the study was evaluated at baseline and again after 5 months. Thirty‐two women received chemotherapy during the study. RESULTS Over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
129
4
24

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 49 publications
13
129
4
24
Order By: Relevance
“…Similarly, time since diagnosis did not correlate significantly with body image concerns, also contrary to the results of Hopwood et al (2001), which found higher scores after 6 months from the time of first surgery. Research on this matter is not consistent, as some studies indicate a better body image soon after diagnosis and a worsening with time (Bloom et al, 1998;Hartl et al, 2003), others report a significant improvement in body image over time (Arora et al, 2001;Ganz et al, 1992b) and others demonstrate a stability on body image through the disease (DeFrank et al, 2007). This inconsistency may be due to the different measures of body image that were used and not to the real effect of time.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, time since diagnosis did not correlate significantly with body image concerns, also contrary to the results of Hopwood et al (2001), which found higher scores after 6 months from the time of first surgery. Research on this matter is not consistent, as some studies indicate a better body image soon after diagnosis and a worsening with time (Bloom et al, 1998;Hartl et al, 2003), others report a significant improvement in body image over time (Arora et al, 2001;Ganz et al, 1992b) and others demonstrate a stability on body image through the disease (DeFrank et al, 2007). This inconsistency may be due to the different measures of body image that were used and not to the real effect of time.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that women with a mastectomy were more likely to report body image dissatisfaction than those with breast conserving treatment (Beckmann et al, 1983;Steinberg et al, 1985;Ganz et al, 1992;Yurek et al, 2000;Lee et al, 1992;Schain et al, 1994;Taylor et al, 2002;Arora et al, 2001;Polivy, 1977;Avis et al, 2004), while other studies did not find type of surgery to be a significant problem (Wolberg et al, 1989;Ashcroft et al, 1985;Penman et al, 1986;Goldberg et al, 1992;Holmberg et al, 1989). Length of time since treatment can be a factor in how women feel about their appearance.…”
Section: Body Image Sexuality and Sexual Problemsmentioning
confidence: 99%
“…Sexual functioning declined during the first year after breast cancer treatment with chemotherapy in three studies (Ganz et al, 2004;Yurek et al, 2000;Arora et al, 2001). During the first six months after treatment Ganz et al (2004) found that sexual functioning was worse for women who received chemotherapy than for those who did not, regardless of type of surgery.…”
Section: Body Image Sexuality and Sexual Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery for gynaecologic cancers may involve the removal of parts of the body involved in sexual arousal (Stead, 2003), and chemotherapy in particular often results in fatigue which affects both sexual functioning and interest (Arora et al, 2001). There is a lack of research into the effects of physical activity in this area with cancer survivors, but Dahn et al (2005) found that sexual functioning was positively associated with PA levels in a sample of prostate cancer survivors who had undergone radiation therapy, and there is also evidence which links physical activity to improved sexual functioning in the general population (Bacon et al, 2003;Hsiao et al, 2012;Laumann et al, 2005).…”
Section: Physical Healthmentioning
confidence: 99%